Determinants of Corporate Income Tax Revenue in Post-Reform Indonesia: A Case Study of the Foreign Investment Tax Office One - Yaumil Fitriyah; Tony Sudirgo (Manunggal Halim Jaya, 2026)
This study examines the impact of taxpayer compliance, tax audits, and tax collection on Corporate Income Tax revenue at the Foreign Investment Tax Office One (Indonesia) between 2022 and 2024. Because taxes act as the primary source of national income, maximizing these funds requires robust voluntary compliance from corporate entities alongside the efficient execution of auditing and collection strategies by tax authorities. To evaluate these factors, this study utilizes a quantitative methodological approach, relying on secondary data gathered from official records. A purposive sampling technique was deliberately employed to ensure the relevance of the selected data points. Subsequently, the data was analyzed using multiple linear regression. Despite previous studies identifying compliance and law enforcement as key drivers of tax revenue, empirical evidence regarding their interplay in a post-tax reform context remains fragmented. Addressing this research gap, this study examines the impact of taxpayer compliance, tax audits, and tax collection on Corporate Income Tax revenue at the Foreign Investment Tax Office One (Indonesia) between 2022 and 2024. This specific period was selected to capture the dynamics following the implementation of the Harmonization of Tax Regulations Law (Law Number 7 of 2021). The empirical findings of this study offer compelling evidence regarding the interplay of these variables. Ultimately, the results of the study indicate that taxpayer compliance, tax audits, and tax collection have a positive effect on Corporate Income Tax revenue. The findings underscore the complementary nature of the Ability to Pay Theory and the Public Enforcement of Law Theory in modern tax administration.